Autosomal dominant optic atrophy with asymptomatic peripheral neuropathy. Issue 2 (February 1996) - Chalmers, R M; Bird, A C; Harding, A E
Abstract : The association between hereditary motor and sensory neuropathy (HMSN) and optic atrophy has been termed HMSN type VI. The autosomal dominant inheritance of this syndrome is reported. Three generations were affected with optic atrophy, which differed in some respects from classic dominant optic atrophy, and an asymptomatic, mainly sensory, neuropathy.